Pies & tarts : for all seasons - Rigg, Annie; Rothacker, Nassima (London : Quadrille, 2018)
"This title features 100 pies and tarts, themed by size: individual tartlets and handheld pies, medium ones for lunch and dinner, and big, celebratory pies for larger gatherings. Sweet and savory recipes for every season, and ideas for super decorative pastry-work as popularized on Instagram. Separate recipes for doughs and crusts made with a variety of flours are also included"--Amazon.com.
Just one Slice -- Pastry 101 -- Sweet -- Savoury -- Index -- Acknowledgements
Include index.
106740
Keywords: Pies; Cookbooks